(untitled) (XXI Century. Spanish Literature and Culture, 2013)
This article focuses on the most noticeable works of published poetry within the Spanish literary milieu of 2012. In addition to examining the contributions of authors already established as innovators of their craft and highlights the distinct tendencies that characterise the poetic evolution taking place in Spain today.